Silencing of circRNA circ_0001666 Represses EMT in Pancreatic Cancer Through Upregulating miR-1251 and Downregulating SOX4 - Zhang, Rundong; Zhu, Wanli; Ma, Chenchao; Ai, Kaixing (Frontiers in Molecular Biosciences, 2021)
Background Pancreatic cancer (PC) is an aggressive malignancy and has a poor prognosis. Although emerging research has revealed that circular RNAs (circRNAs) are crucial modulators that control tumor development and metastasis, their functional involvement in PC has not been well characterized. Here, we examined whether and how circRNA circ_0001666 governs epithelial-mesenchymal transition (EMT) in PC. Methods We investigated the effects of circ_0001666 on EMT and PC cell invasion by gain- and loss-of-function assays. We also explored the mechanisms underlying the functions of circ_0001666 in PC cells. Results We found that circ_0001666 is highly expressed in PC tissues and PC cell lines. Patients with high circ_0001666 expression had shorter survival times. In vitro and in vivo experiments have demonstrated that upregulation of circ_0001666 facilitates PC cell proliferation, EMT and invasiveness, whereas knockdown of circ_0001666 exhibits opposite functions. Moreover, circ_0001666 is able to bind to miR-1251, thus increasing the expression of SOX4, which is a direct downstream effector of miR-1251. The oncogenic effects of circ_0001666 on EMT and PC cell invasion were rescued by miR-1251 overexpression. Conclusions These results suggested that circ_0001666 acts as an oncogenic circRNA to promote EMT and invasion of PC cells through sponging miR-1251, and indicated that circ_0001666 could be explored as a potential therapeutic target for PC.